PARTICIPATION OF MICROORGANISMS IN THE FORMATION OF TRAVERTINES AND SAPROPELITE KEROGEN IN SEDIMENTS OF THERMAL CARBONIC WATERS IN THE BAIKAL RIFT ZONE - Tatarinov A.V.; Yalovik L.I.; Danilova E.V.; Namsaraev Z.B. (My University, 2006)
The geomicrobiological study of travertine sediments from hot springs of nitrogen sodium–sulfate waters in the Baikal rift zone demonstrated the decisive role of cyanobacterial mats in their formation. At the same time, the mechanism of decompression formation without the participation of microorganisms is assumed for travertines that are widespread in the East Sayan terrain of hot and cold carbonic waters.